Board attributes and financial distress during health crisis: evidence from Malaysia / Muhammad Azreey Zaki ... [et al.] - Zaki, Muhammad Azreey; Mohd Suffian, Mohd Taufik; Mohamad Ariff, Akmalia; Nustini, Yuni (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
This study explored how corporate governance mechanisms influence the financial distress of companies listed on Bursa Malaysia. The sample comprised 590 companies from the Bursa Malaysia Main Market during 2020- 2021. The study examined the impact of corporate governance elements (board gender diversity, foreign directorship, and expertise, size, meeting, and independence) on financial distress, the latter being the dependent variable. While the COVID-19 pandemic impacted various aspects of businesses, including performance, governance, dividends, liquidity, and debt, the specifics of its effects are not well-established. The research indicated that the expertise of boards had a significant negative effect on financial distress, while gender diversity and foreign directorship, boards’ size, meetings, and independence had positive impacts. However, board size, board meetings, and board independence were insignificant. This study contributes empirical evidence on the relationship between corporate governance and financial distress during Malaysia's COVID-19 pandemic, filling a gap in the existing literature. Importantly, it offers practical insights for decision-makers in emerging economies regarding board composition and responsibilities that support governance mechanisms and mitigate financial distress.